Oral health practices and literacy in Hungarian diabetes patients: insights from a pilot-study using a WHO-adapted questionnaire - Klaudia Lipták; Laura Lipták; Kata Sára Haba; Dorottya Bányai; Dániel S. Veres; Noémi Katinka Rózsa; Péter Hermann; Dániel Végh (BMC Oral Health)
Abstract Introduction This study aimed to compare the self-reported oral health status, knowledge, and habits of individuals living with diabetes mellitus and healthy controls. To achieve this, the modified version of the World Health Organization’s Oral Health Questionnaire for Adults (ANNEX 7; Google Forms) was employed for data collection. Methods The study included 99 diabetes patients (33 with type 1 and 66 with type 2 diabetes mellitus) and 102 non-diabetic controls. Logistic regression models, adjusted for demographic factors, were applied to examine associations between oral hygiene practices, dietary habits, and the number of natural teeth. Results Individuals with diabetes exhibited a greater frequency of oral pathological conditions. Despite 74% of people with diabetes mellitus (PwDM) brushing their teeth twice daily, they had fewer natural teeth compared to the control group (20 or more teeth: DM: 54.5%, controls: 70.6%). In our study, there is no evidence that number of teeth is dependent on HbA1c levels, and we found that neither age nor gender influenced the change in HbA1c levels. Lower interdental cleaning habits and frequent fruit consumption were identified as significant risk factors for severe tooth loss. Conclusion and clinical relevance This study highlights significant oral health disparities in diabetes patients, particularly those with T2DM, who reported poorer oral health, more frequent denture use, and fewer natural teeth. These findings underscore the need for integrating oral health education, preventive care, and interdisciplinary collaboration into diabetes management to improve overall health outcomes.